Analysis of Tendencies in WEB Based Technology Education of Undergraduate Students in Turkey - (:unkn) unknown (DRUNPP-SARAJEVO, 2011)
In our developing world, rise in population leads to increase in needs and demands. One of these increasing needs is the increase in demand for education and training. Although states have allocated greater amounts of fund from their budget every year, the problem has not been solved yet and students have outgrown the classes. :Especially developed countries have been trying to find solutions for these problems which cannot be solved with traditional methods by aiming at distance learning. In this study, distance learning is explained and its disadvantages and advantages compared to traditional education is dwelled on. History of distance learning has been examined and distance teaming practices both in our country and in the world have been discussed. In this study, field research is done by using survey method since the aim of this research is to put forward the tendencies of the students in Marmara University Technical Education Faculty towards web- based technology education. Total number of respondents of this survey is 319, 25 of which is female and 294 of which is male. Statistical tables are obtained by computerizing the results of the survey and analysing them by using Statistical Package for the Social Sciences (SPSS). In order to determine the difference among the variables one-way analysis of variance and to determine the source of difference Scheffe Test are used. It has been found out that dependent variables show significant differences when compared to independent variables; there are significant differences in students due to sex, age, class, department, having information about distance learning and being educated by distance learning. All the data obtained have been interpreted and suggestions have been given according to these data and results obtained.
Keywords: Web Based Education; Technical Education; Technology Education